Modulation of lethal HPAIV H5N8 clade 2.3.4.4B infection in AIV pre-exposed mallards - Koethe, Susanne (Emerg Microbes Infect, 2020)
In 2016/2017, a severe epidemic of HPAIV H5N8 clade 2.3.4.4 group B (H5N8B) affected Europe. To analyse the role of mallards in the spatiotemporal dynamics of global HPAIV H5N8B dispersal, mallards (Anas platyrhynchos), naturally exposed to various AIV and therefore seropositive, were challenged with H5N8B. All experiments were controlled by infection and co-housing of seronegative juvenile Pekin ducklings. All ducks that survived the first infection were re-challenged 21 dpi with the homologous H5N8B strain. After the first H5N8B infection, seropositive mallards showed only mild clinical symptoms. Moderate to low viral shedding, occurring particularly from the oropharynx and lasting for 7 days maximum, led to severe clinical disease of all contact ducklings. All challenged seronegative Pekin ducks and contact ducklings died or had to be euthanized. H5-specific antibodies were detected in surviving birds within 2 weeks. Virus and viral RNA could be isolated from several water samples until 6 and 9 dpi, respectively. Conversely, upon re-infection with homologous H5N8B neither inoculated nor contact ducklings showed any clinical symptoms, nor was an antibody titer increase of seropositive mallards or any seroconversion of contact ducklings observed. Mallard ducks naturally pre-exposed to LPAIV can play a role as a clinically unsuspicious virus reservoir for H5N8B effective in virus transmission. Mallards with homologous immunity did not contribute to virus transmission.